Report of Four Cases of Disease Vogt - Koyanagi - Harada - González, César A. (1963)
Three cases of Harada's disease and one case of Vogt- Koyanagi syndrome are reported. All these cases exhibit the characteristics of this entity. All cases were treated with systemic and topical cortisone , which seems to be useful . Excellent results (recovery of central and peripheral vision) , were obtained in these patients. The only complication with regard to therapy was an acute episode of psychosis in patient No. 3 which came after acute administration of cortisone ; it disappeared completely 3 weeks after drug taper . It has been reported that Harada 's disease and Vogt- Koyanagi syndrome occur in patients highly pigmented . It is interesting to note that two of the four cases were presented in white people . The literature review shows that the disease is sporadic , with no apparent relation to the seasons or geographic area. Encephalopathy syndrome uveo - dermatosis : a new term that typifies the clinical course suggested.